Co-expression and co-responses: within and beyond transcription - Tohge, Takayuki; Fernie, Alisdair R. (Frontiers in Plant Science, 2012)
Whole genome sequencing, the relative ease of transcript profiling by the use of microarrays and latterly RNA sequencing approaches have facilitated the capture of vast amounts of transcript data. However, despite the enormous progress made in gene annotation a substantial proportion of genes remain to be annotated at the functional level. Considerable progress has, however, been made by searching for transcriptional coordination between genes of known function and non-annotated genes on the premise that such co-expressed genes tend to be functionally related. Here we review progress made following this approach as well as its expansion to include phenotypic information from other levels of cellular organization such as proteomic and metabolomic data as well as physiological and developmental phenotypes.